An Application of the Team Quiz Learning Model to Improving Cooperation Capabilities in Elementary School - Erza Lina; Iis Aprinawati; Mufarizuddin Mufarizuddin (Edumaspul: Jurnal Pendidikan, 2022)
Abstract. This research is motivated by the low cooperation skills of fifth grade students at SDN 024 Limau Manis. One solution to overcome this problem is to apply the team quiz model. The purpose of this study was to describe increasing student collaboration by applying the team quiz model to the fifth grade students of SDN 024 Limau Manis. This research method is classroom action research (PTK) which is carried out in two cycles. Each cycle consists of two meetings and four stages, namely planning, implementation, observation and reflection. The subjects of this study were fifth grade students, totaling 15 students. Data collection techniques in the form of documentation, observation and tests. this is indicated by an increase in the number of students who reach the minimum completeness criteria (KKM). Before action 33.3%, cycle I meeting I 33.3% and cycle I meeting II 33.3% and increased in cycle II meeting I to 66.7%, and cycle II meeting II 100%. Keywords: Model Team Quiz and Cooperation